Functional Evaluation of Major Salivary Glands Using Viscosity PLUS and 2D Shear-Wave PLUS Elastography Techniques in Healthy Subjects—A Pilot Study - Muntean, Delia Doris; Lenghel, Manuela Lavinia; Petea-Balea, Diana-Raluca; Ciurea, Anca Ileana; Solomon, Carolina; Dudea, Sorin Marian (Diagnostics (Basel), 2022)
Biological soft tissues are characterized by viscoelastic properties. The propagation of shear waves within tissues is influenced by both elasticity, which is linked to the shear wave speed, and viscosity, which is linked to the shear wave dispersion. This study aimed to functionally assess the parotid glands (PG) and submandibular glands (SMG) in a group of 40 healthy subjects using the novel Viscosity PLUS (Vi.PLUS) and 2D Shear-Wave Elastography PLUS (2D-SWE.PLUS) techniques. The viscosity and stiffness of PG and SMG were measured before and after gustatory stimulation with a sialagogue agent (commercially available lemon juice) using the new SuperSonic MACH 30 ultrasound system equipped with a curvilinear C6-1X transducer. PG presented a mean basal viscosity and elasticity of 2.10 ± 0.19 Pa.s and 11.32 ± 1.91 kPa, respectively, which significantly increased poststimulation to 2.39 ± 0.17 Pa.s (p < 0.001) and 12.58 ± 1.92 kPa (p < 0.001), respectively. SMG did not present statistically increased values of viscosity and elasticity following stimulation (2.31 ± 015 Pa.s vs. 2.37 ± 0.18 Pa.s, p = 0.086, and 10.40 ± 1.64 kPa vs. 10.90 ± 1.98 kPa, p = 0.074, respectively). Vi.PLUS measurements presented a good positive correlation with 2D-SWE.PLUS values for PG and SMG, before and after stimulation. Gender and BMI were not confounding factors for these two parameters. Vi.PLUS represents an innovative non-invasive imaging technique that, together with 2D-SWE.PLUS proves to be useful in functionally assessing the major salivary glands in healthy subjects.